Monitoring agriculture sector performance in Swaziland: Investment, growth and poverty trends, 2000—2011 - Musaba, Emmanuel; Pali-Shikhulu, John; Chilonda, Pius; Nhlengethwa, Sibusiso B.; Matchaya, Greenwell C. (International Water Management Institute, 2014)
This first annual trends and outlook (ATOR) report for Swaziland assesses the performance of the agriculture sector in terms of investment, growth, and poverty and hunger outcomes over the period 2000–2011. The need for monitoring arises from the fact, that Swaziland and other African countries need to regularly assess whether or not they are making good on their commitments in terms of national development targets and regionally agreed development targets; and provide such information to various state and non–state actors and stakeholders at national and regional levels.